Will Gravitational Wave Sirens Determine the Hubble Constant? [Article] - Shafieloo, Arman; Keeley, Ryan E.; Linder, Eric V. (NURIS; Energetic Cosmos Laboratory, 2018)
Lack of knowledge about the background expansion history of the Universe from independent observations makes it problematic to obtain a precise and accurate estimation of the Hubble constant H0 from gravitational wave standard sirens, even with electromagnetic counterpart redshifts. Simply fitting simultaneously for the matter density in a flat \lcdm\ model can reduce the precision on H0 from 1\% to 5\%, while not knowing the actual background expansion model of the universe (e.g.\ form of dark energy) can introduce substantial bias in estimation of the Hubble constant. When the statistical precision is at the level of 1\% uncertainty on H0, biases in non-\lcdm\ cosmologies that are consistent with current data could reach the 3σ level. To avoid model-dependent biases, statistical techniques that are appropriately agnostic about model assumptions need to be employed.
Energetic Cosmos Laboratory. ECL Publication, 2019
Keywords: The 2nd international conference of the Energetic Cosmos Laboratory (ECL); Energetic Cosmos Laboratory (ECL); ECL19